Drivers of richness and community composition of fungal endophytes of tree seeds. Issue 9 (20th August 2020) - Franić, Iva; Eschen, René; Allan, Eric; Hartmann, Martin; Schneider, Salome; Prospero, Simone
ABSTRACT: Recent studies revealed a high diversity of fungal endophytes in traded tree seeds, including potential plant pathogens. The factors determining richness and composition of seed mycobiomes are poorly understood, but might be an important determinant for tree health. We assessed the relative impact of host identity, site, several site-specific environmental factors, and whether the host was sampled in its native or non-native distribution range, on the richness and composition of fungal seed endophytes of nine tree species across 15 sites in Europe and North America. Our results show that fungal richness was affected by host identity, but not by environmental variables or host distribution range. Fungal community composition was primarily driven by host identity, and to a lesser extent by environment. Around 25% of the 2147 amplicon sequence variants (ASVs) were generalists appearing on both continents and in both gymnosperms and angiosperms. Around 63% of the ASVs appeared in only gymnosperms or angiosperms, and 33% of the ASVs were associated with a single host species, while none were found in all tree species. Our results suggest that although seed trade might facilitate movements of fungi, their establishment and spread in the new environment might be limited by host availability. Abstract : Host identity is the key driver of richness and community composition of fungal endophytes of tree seeds.